Farmers' Participation and Its Implications for Farms' Economic Viability in Collectively Managed Irrigation Systems: A Case Study in Pakistan - Riaz, M.; Ashfaq, M.; Boz, I.; Shahbaz, P.; Bin Khalid, U. (Tarbiat Modares Univ, 2023)
Participatory Irrigation Management (PIM) has emerged as a significant intervention in which farmers are given more control over irrigation management. The primary goal of this study was to identify the factors that influence farmers' participation in PIM activities and compare the economic viability of participation levels. A multi-stage random sampling technique was used to collect the data from 240 farmers of Nasrana and Maduana distributaries located at the tail end of the Lower Chenab Canal (LCC) west circle in district Faisalabad, Punjab, Pakistan, using a structured questionnaire. The factors influencing farmers' participation in PIM activities were identified using an ordered Probit Regression model. The findings revealed that education level (beta= 0.12; P=0.00), village leadership (beta= 0.97; P= 0.00), and being a beneficiary of a water user association (beta=1.20; P= 0.00) all had a significant positive influence on farmers' participation in PIM activities. On the other hand, family size (beta=-0.05 P= 0.04), land ownership (beta=-0.44; P= 0.05), and off-farm income (beta=-0.52; P= 0.01) were found to have a significant negative impact on farmers' participation. Farmers with a high level of participation had higher farm technical efficiency and crop productivity. For these reasons, farming communities must be encouraged to participate in PIM activities in order to achieve a sustainable irrigation system.
Keywords: Irrigated Agriculture; Pakistan; Participatory Irrigation Management System; Technical Efficiency